2018
DOI: 10.1115/1.4041710
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Sequential Prediction of Cutting Force Using Kienzle Model in Orthogonal Turning Process

Abstract: Probabilistic sequential prediction of cutting forces is performed applying Bayesian inference to Kienzle force model. The model uncertainties are quantified using the Metropolis algorithm of the Markov chain Monte Carlo (MCMC) approach. Prior probabilities are established and posteriors of the models parameters and force predictions are completed using the results of orthogonal turning experiments. Two types of tools with chamfer (rake) angles of 0 deg and −10 deg are tested under various cutting speed and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Since chip geometry is also of great importance in this calculation, the chip cross-section area (A0) is calculated by multiplying the depth of cut (ap) and the feed rate (f) according to Equation 9. In Equation 9, a p represents the depth of cut (mm) and f represents the feed rate (mm/rev). 28 In the study conducted according to these calculations, it was observed that the chip cross-section area would decrease by decreasing the ap and f in Equation 9. Accordingly, the decreasing cross-section area and constant specific cutting resistance in Equation 8 would cause Fc to decrease.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Since chip geometry is also of great importance in this calculation, the chip cross-section area (A0) is calculated by multiplying the depth of cut (ap) and the feed rate (f) according to Equation 9. In Equation 9, a p represents the depth of cut (mm) and f represents the feed rate (mm/rev). 28 In the study conducted according to these calculations, it was observed that the chip cross-section area would decrease by decreasing the ap and f in Equation 9. Accordingly, the decreasing cross-section area and constant specific cutting resistance in Equation 8 would cause Fc to decrease.…”
Section: Resultsmentioning
confidence: 98%
“…In Equation 9, a p represents the depth of cut (mm) and f represents the feed rate (mm/rev). 28 In the study conducted according to these calculations, it was observed that the chip cross-section area would decrease by decreasing the ap and f in Equation 9. Accordingly, the decreasing cross-section area and constant specific cutting resistance in Equation 8 would cause Fc to decrease.…”
Section: Power Consumptionmentioning
confidence: 98%
“…Based on a predictive machining theory, Fu et al [18] proposed a cutting force model for turning, which adopted the non-equidistant shear zone model and regarded the cutter geometry and processing conditions as the entering information. Salehi et al [19] performed the cutting force forecast by employing Bayesian inference in the cutting force model. A consecutive force forecast was performed by employing the posterior probabilities of the model arguments.…”
Section: Introductionmentioning
confidence: 99%
“…Hui W [7] established the mechanism model of cutting forces in the feed direction of CFRP composite end face grinding with horizontal ultrasonic vibration, and established a mechanical model based on toughness model. Salehi M [8] proposed cutting forces prediction using Bayesian inference (MCMC simulation) for the Merchant and Kienzle force models. John M [9] developed a new energy dissipation mechanism, improving the previously derived steady-state cutting force analysis model, to improve the predictive ability of high blade cutting conditions.…”
Section: Introductionmentioning
confidence: 99%